Nietzsche on Time and History. - Dries, Manuel (Walter de Gruyter, 2008)
In 1885 Nietzsche insisted that from now on philosophy was only acceptable?as the most general form of history, as an attempt somehow to describe Heraclitean becoming and to abbreviate it into signs.? Taking this remark as a starting point, the aim of this volume is to examine the intricate relationship between Nietzsche?s philosophy of time and his philosophy of history. The questions that arise include: What are the new conceptions of time that Nietzsche has to offer? What kind of historian was Nietzsche himself? What kinds of temporalized histories and historicized philosophies did he writ.